2023
DOI: 10.1007/s12028-023-01700-w
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Autoregulation, Cerebral Hemodynamics, and Injury Biomarkers, in Patients with COVID-19 Treated with Veno-Venous Extracorporeal Membrane Oxygenation

Abstract: Background This study aimed to describe the cerebrovascular dynamics, in particular cerebral autoregulation (CA), and cerebral biomarkers as neuron-specific enolase (NSE) in patients with a diagnosis of coronavirus disease 2019 and acute respiratory distress syndrome as well as undergoing veno-venous extracorporeal membrane treatment. Methods This was a single center, observational study conducted in the intensive care unit of the University Hospital in Wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
1
4
0
Order By: Relevance
“…PRx was correlated with NSE and GFAP; therefore, impaired cerebral autoregulation (indicated by a higher PRx) was associated with increased levels of NSE and GFAP. This observation is consistent with our previous research, where we found a positive relationship between NSE and cerebral autoregulation [81]. Previous studies have also indicated that cerebral autoregulation is related to inflammation-related blood biomarkers [82].…”
Section: Discussionsupporting
confidence: 93%
“…PRx was correlated with NSE and GFAP; therefore, impaired cerebral autoregulation (indicated by a higher PRx) was associated with increased levels of NSE and GFAP. This observation is consistent with our previous research, where we found a positive relationship between NSE and cerebral autoregulation [81]. Previous studies have also indicated that cerebral autoregulation is related to inflammation-related blood biomarkers [82].…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we observed an equal incidence of cerebral pathologies in both groups. Impaired cerebral autoregulation has been proposed previously in SARS-CoV-2 infection in single cases and small series ( 4 , 7 ). Schramm et al ( 16 ) showed that severe sepsis is associated with impaired cerebral autoregulation using a transcranial doppler sonography-derived autoregulation index.…”
Section: Discussionmentioning
confidence: 62%
“…Similar results are reported by Crippa et al ( 17 ), showing that 50% of patients with sepsis exhibit impaired cerebral autoregulation which is associated with brain dysfunction. Burzynska et al ( 7 ) reported in a series of 16 SARS-CoV-2 patients with ARDS undergoing vv-ECMO therapy that these patients are likely to experience both elevated biomarkers of cerebral damage and impairment of cerebral autoregulation. We can essentially confirm these findings with the additional finding that there is a difference in cerebral autoregulation between SARS-CoV-2 and non SARS-CoV-2 patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At day 5, 26 proteins were differentially expressed with respect to the overall virus effect that were not altered at day 2. Some of these proteins were associated with adhesion [Clmp: Coxsackie- And Adenovirus Receptor-Like Membrane Protein ( 44 ); Itgb6, integrin subunit beta 6; Itgb1bp2, integrin subunit beta 1 binding protein 2; Mia, melanoma inhibitory activity protein ( 45 ); Matn2, matrilin 2 ( 46 )], cardiac function [Fstl3, follistatin like 3 ( 47 ); Tnni3, troponin I type 3 cardiac], and neurological function [Eno2, enolase 2/neuron-specific enolase ( 48 ); Gdnf, glial cell-derived neurotrophic factor; Ntf3, neurotrophin 3; Gfra1, glial cell-derived neurotrophic factor (GDNF) family receptor alpha 1 ( 49 ); Clmp ( 44 ); and Matn2 ( 46 )].…”
Section: Resultsmentioning
confidence: 99%